AN ANALYSIS OF GENERATION MEANS FOR SEED YIELD AND ITS COMPONENTS IN LINSEED - KASHYAP, O. P.; RASTOGI, N.K. (Annals of Agricultural Research, 2014)
Five generations (P1 P2, F1, F2 and F3) of seventeen linseed crosses, were raised in randomized block design with three replications. The means of the five generations recorded for oil content, seed yield and its contributing traits, were subjected to C-scaling test as suggested by Mather (1949) and fiveparameter model of Hayman (1958) to detect epistasis and estimates of (m), (d), (h), (i) and (1) parameters. There was evidence of epistasis for all the eight traits. Additive gene effect along with epistasis predominantly governed the expression of oil content while non-additive gene effect with epistasis was predominant in number of branches plant-1, number of capsules plant-1 and seed yield plant-1. Days to maturity, number of seeds capsule-1, seed index and harvest index were under the control of both additive and non-additive gene effects together with non-allelic interactions viz., additive x additive and dominance x dominance. A predominance of complementary type of epitasis was observed for number of capsules plant-1, seed yield plant-1, harvest index and oil content followed duplicate type.